Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Sanksi Perpajakan Sebagai Variabel Moderating (Studi Empiris Pada Wajib Pajak Orang Pribadi Di Kota Mataram) - Ghassani, Nadhila (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
This research aims to analyze the factors that influence of taxpayers awareness, quality of services, tax knowledge, tax sanctions of taxpayers compliance. The sample of this research are individual taxpayers that taken randomly in Mataram City. This research is also using tax sanctions as a moderating variable.Â  The respondents from this research are 150 respondents. Data analysis method that used in this research are Moderated Regression Analysis (MRA) and performed using SPSS for Windows.The results of this research indicated that awareness of taxpayers, quality of services, tax knowledge have a positive and significant influence of taxpayers compliance. Tax sanctions variable as a pure moderator that strenghten the relationship between dependent variable and independent variables. Keyword: Taxpayers Awareness, Quality of services, Tax knowledge, Tax sanctions, Taxpayers compliance